Cu@Co-MOFs as a novel catalyst of peroxymonosulfate for the efficient removal of methylene blue. Issue 17 (25th March 2019) - Li, Huanxuan; Xu, Shaodan; Du, Jia; Tang, Junhong; Zhou, Qingwei
Abstract : In this study, for the first time, we describe the single step synthesis of a Cu particle-doped cobalt-based metal–organic framework (Cu@Co-MOF) using a hydrothermal method. Abstract : In this study, for the first time, we describe the single step synthesis of a Cu particle-doped cobalt-based metal–organic framework (Cu@Co-MOF) using a hydrothermal method. The as-prepared materials were characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy-energy disperse spectroscopy, thermogravimetry, and X-ray photoelectron spectroscopy, which confirmed the incorporation of zero-valent copper on the surface of the Co-MOFs. The heterogeneous catalytic activity of Cu@Co-MOFs was tested to activate peroxymonosulfate (PMS) for the removal of methylene blue (MB). The ratio of n (Cu)/ n (Co) in the Cu@Co-MOFs showed a strong impact on the catalytic activity of the Cu@Co-MOFs, whereas a n (Cu)/ n (Co) of 1 : 1 exhibited the best catalytic performance and obtained 100% MB removal within 30 min. The effects of initial pH, reaction temperature, PMS concentration, and catalyst dosages were investigated in this study. The stability and reusability of the Cu@Co-MOFs were also investigated. The results showed a low decline in the MB removal with the increase in cycle numbers, whereas 100% MB was removed by prolonging the reaction time. Heterogeneous reactions taking place in the pores and surface of the Cu@Co-MOFs played an important role in the generation of the sulfate radicals (SO4 ˙ − ) and hydroxyl radicals (·OH) that were the primary reactive species responsible for MB degradation.